Tangeretin attenuates bleomycin-induced pulmonary fibrosis by inhibiting epithelial-mesenchymal transition via the PI3K/Akt pathway - Li, Jiang; Wei, Qian; Song, Ke; Wang, Youxin; Yang, Yuxin; Li, Miao; Yu, Jiaying; Su, Guangxu; Peng, Luyuan; Fu, Bendong; Yi, Pengfei (Frontiers in Pharmacology, 2023)
Background: Pulmonary fibrosis (PF) is a terminal pathological change in a variety of lung diseases characterized by excessive deposition of extracellular matrix, for which effective treatment is lacking. Tangeretin (Tan), a flavonoid derived from citrus, has been shown to have a wide range of pharmacological effects. This study aimed to investigate the role and potential mechanisms of Tan on pulmonary fibrosis. Methods: A model of pulmonary fibrosis was established by administering bleomycin through tracheal drip, followed by administering Tan or pirfenidone through gavage. HE and Masson staining were employed to assess the extent of pulmonary fibrosis. Subsequently, Western blot, enzyme-linked immunosorbent assay (ELISA), RNA sequencing, and immunohistochemistry techniques were employed to uncover the protective mechanism of Tan in PF mice. Furthermore, A549 cells were stimulated with TGF-β1 to induce epithelial-mesenchymal transition (EMT) and demonstrate the effectiveness of Tan in mitigating PF. Results: Tan significantly ameliorated bleomycin-induced pulmonary fibrosis, improved fibrotic pathological changes, and collagen deposition in the lungs, and reduced lung inflammation and oxidative stress. The KEGG pathway enrichment analysis revealed a higher number of enriched genes in the PI3K/Akt pathway. Additionally, Tan can inhibit the EMT process related to pulmonary fibrosis. Conclusion: Taken together, the above research results indicate that Tan suppresses inflammation, oxidative stress, and EMT in BLM-induced pulmonary fibrosis via the PI3K/Akt pathway and is a potential agent for the treatment of pulmonary fibrosis.